2008
DOI: 10.1103/physreve.78.030701
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity-mediated nematiclike bacterial organization in model extracellular DNA matrix

Abstract: DNA is a common extracellular matrix component of bacterial biofilms. We find that bacteria can spontaneously order in a matrix of aligned concentrated DNA, in which rod-shaped cells of Pseudomonas aeruginosa follow the orientation of extended DNA chains. The alignment of bacteria is ensured by elasticity and liquid crystalline properties of the DNA matrix. These findings show how behavior of planktonic bacteria may be modified in extracellular polymeric substances of biofilms and illustrate the potential of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 36 publications
3
85
1
1
Order By: Relevance
“…P. aeruginosa cells have been shown to spontaneously orient with the direction of extended, concentrated DNA molecules (35). Our time-lapse imaging of interstitial biofilm expansion in the presence of the eDNA stain TOTO-1 revealed that as cells migrated through areas of high eDNA content, they dragged the eDNA along, causing it to be generally aligned with the direction of cell movement (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…P. aeruginosa cells have been shown to spontaneously orient with the direction of extended, concentrated DNA molecules (35). Our time-lapse imaging of interstitial biofilm expansion in the presence of the eDNA stain TOTO-1 revealed that as cells migrated through areas of high eDNA content, they dragged the eDNA along, causing it to be generally aligned with the direction of cell movement (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…43,44 Additionally, the patterns and order induced in theses LCLC films could be transferred to suspended colloids, suspended nanotubes and bacterial systems to create novel metamaterial films. [21][22][23][24][25] …”
Section: -9 |mentioning
confidence: 99%
“…As a result, their mesophases differ significantly from thermotropic and amphiphilic lyotropic liquid crystals. Patterned films of LCLCs have a wide variety of emerging applications distinct from other types of liquid crystals, including inexpensive polarizing films, [12][13][14] holographic displays, 15,16 organic electronics and solar cells, 17,18 biosensors, 19,20 , aqueous colloidal, nanotube and bacterial assembly, [21][22][23][24][25] and precursors to structured graphene-based materials. 26,27 LCLCs also offer useful attributes for fundamental investigation of the effects of elasticity on self-assembly behavior, since their elastic properties can be tuned via control of mesogen concentration, 28 depletants and ions.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 For the nematic LC, assuming that the Frank elastic constants for splay, twist, and bend are equal to their average value K, the elastic energy cost of rod realignment 23 to an angle θ from its equilibrium θ ) 0 orientation can be estimated as ∆F elastic ≈ 2πKθ 2 L/ln[2L/R] (note that the rods studied here have rather small aspect ratios and only rough estimates are possible by using this equation). Taking K ≈ 1pN (typical for lyotropic nematics) and dimensions of GNRs, one finds ∆F elastic ≈ 3 × 10 -19 θ 2 J larger than the thermal energy K B T unless θ is very small.…”
mentioning
confidence: 99%